A Modified VATS Procedure for Treating Adult Intralobar Pulmonary Sequestration - Zeng, Bo; Zou, Jianyong; Yang, Weixiong; Liu, Zhenguo; Xie, Chunying; Cheng, Chao (The Thoracic and Cardiovascular Surgeon, 2020)
Video-assisted thoracoscopic surgery (VATS) makes it possible to treat intralobar sequestration (ILS) more minimally invasive compared with conventional open surgery. However, this procedure is challenging to expose and isolate the aberrant arteries of ILS and the risk of bleeding is high. Herein, we developed a modified VATS procedure in which the aberrant vessels are treated in the last step of lobectomy, rather than at the beginning. In this way, we can expose the aberrant vessels easier and reduce the risk of massive blood loss, also simplifying the surgical procedure.
Keywords: adult intralobar pulmonary sequestration; surgery; VATS